Comparing objective and subjective measures of journey time accessibility - Angela Curl; John D. Nelson (European Regional Science Association (ERSA), 2010)
This paper presents work undertaken to date as part of PhD research into the process of Accessibility Planning in the UK and how existing objective measures of accessibility relate to individual perceptions or the "lived experience" of accessibility. Since 1997, Accessibility has been framed in the social exclusion context within UK transport planning and policy, focusing on the ability of people to participate fully in society, which is seen as being limited by poor accessibility. This approach recognises that factors other than spatial location are important and places importance on barriers to accessibility such as information, cost and, safety and security as well as provision of transport services and journey times (Social Exclusion Unit, 2003). Despite this recognition, accessibility measures and indicators tend to focus on the objective journey time or distance of people to destinations, and do not consider more subjective factors such as convenience, physical mobility, safety and cost. This research critically appraises dominant approaches to accessibility planning, reviewing current approaches based upon their practicality, data requirements and outcomes, before presenting a mixed methods, case study approach to understand how perceived or "lived" accessibility differs from currently used objective measures. Engagement with practitioners has led to a greater understanding of the requirements of policy makers in improving accessibility and how the process of accessibility planning links to desired policy outcomes. Primary fieldwork involves understanding individual perceptions and subjective accessibilities, to form comparison with existing objective measures of accessibility. This paper will present some preliminary results.
Keywords: 330